2021
DOI: 10.3389/fpsyt.2021.631518
|View full text |Cite
|
Sign up to set email alerts
|

Anosognosia in Mild Cognitive Impairment: Lack of Awareness of Memory Difficulties Characterizes Prodromal Alzheimer's Disease

Abstract: While anosognosia is often present in Alzheimer's disease, the degree of awareness of cognitive difficulties in the earlier stages, such as Mild Cognitive Impairment (MCI), is less clear. Using a questionnaire and Feeling-of-Knowing tasks, the aims of this study were (1) to test the hypothesis that anosognosia is present specifically in prodromal AD stage in patients that, owing to a more severe AD neuropathology, will rapidly progress to overt dementia and (2) to assess the neural bases of self-awareness for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 111 publications
3
36
0
Order By: Relevance
“…PMC hypoactivation appears to be significantly associated with an increased conversion rate from MCI to AD [9][10][11]. PMC is involved in VSWM [18], metamemory [50,67,69], and visuomotor control abilities [22][23][24]. Testing the integrity of this neuropsychological cluster could help clinicians to early discriminate MCI patients who are more likely to convert in probable AD from those who are not [12][13][14], thus orienting further investigations and/or preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PMC hypoactivation appears to be significantly associated with an increased conversion rate from MCI to AD [9][10][11]. PMC is involved in VSWM [18], metamemory [50,67,69], and visuomotor control abilities [22][23][24]. Testing the integrity of this neuropsychological cluster could help clinicians to early discriminate MCI patients who are more likely to convert in probable AD from those who are not [12][13][14], thus orienting further investigations and/or preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As concerns the neurofunctional correlates of anosognosia for memory deficits, it has been recently proposed that decreased connectivity in the fronto-temporo-parietal network, including the medial temporal lobe, would prevent updating of the state of memory functioning, which depends on the experience-based knowledge accumulated through the continued exposure to memory successes or failures. Conversely, abnormal activity in medial-frontal and -parietal regions would affect online monitoring and evaluation of cognitive performance [67]. Recent neuroimaging studies showed that greater anosognosia for memory deficits in amnestic MCI was associated with (1) hypometabolism in posterior and middle cingulate cortices, inferior parietal lobule, precuneus, angular gyrus [50,69], hippocampus [49,50], and (2) reduced functional connectivity between the posterior cingulate cortex, orbitofrontal cortex and inferior parietal lobe [50].…”
Section: And Anosognosia For Memory Deficitsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is emerging evidence that metacognition may be affected even in the early stages of prodromal neurodegeneration. Those with mild cognitive impairment (MCI) and impaired metacognition are more likely to progress to future dementia than those with intact awareness [3]. How metacognition for different cognitive domains changes over the course of neurodegeneration is unclear, and is an understudied topic.…”
Section: Introductionmentioning
confidence: 99%